Determination of Acute Effects of 2,4-Dichlorophenoxyacetic Acid on Antioxidant Enzymes and Lipid Peroxidation Levels in Zebrafish (Danio rerio Hamilton, 1822) Gills - Figen Esin Kayhan; Güllü Kaymak; Cansu Akbulut; Nazan Deniz Yön Ertuğ (Trakya University Journal of Natural Sciences, 2017)
The aim of this study is to determine the potential of 2,4-D (2,4-Dichlorophenoxyacetic acid) herbicide in causing acute oxidative stress in the gills of zebrafish (Danio rerio Hamilton, 1822) using spectrophotometric methods. Test animals except the control group (Group-K) were exposed to sublethal doses (0.1ppm, 0.5ppm and 1ppm) of 2,4-D herbicide for 96 hours. Malondialdehyde (MDA) was used to determine lipid peroxidation levels, and reduced glutathione (GSH), catalase enzyme activity (CAT) and total protein (TP) levels were determined to determine their effects on antioxidant systems in gill tissues. In this study, total protein levels in gills of zebrafish exposed to sublethal doses of 2,4-D were observed to be reduced compared to the control group. MDA levels significantly increased compared to the control group. GSH levels increased in the highest dose of 2,4-D herbicide but decreased in other doses. No significant difference was found in CAT activity compared to the control group.